Temporary plugging agent for plugging drilling cracks in oil exploitation and preparation method of temporary plugging agent

By using calcium carbonate particles, resin particles and long-length cotton fibers in the oil mining drilling temporary plugging agent, the electrostatic adsorption and adhesion ability of the temporary plugging agent is improved, and the problem of well wall powder particles affecting the sealing effect is solved, and the realization of the realization of the sealing effect of the well wall powder particles is achieved. Improved sealing time and compressive resistance.

CN119320625AInactive Publication Date: 2025-01-17SHAANXI HEXIN ZHONGYI OIL & GAS TECH SERVICE CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411869009.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-01-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When using the existing oil mining drilling temporary plugging agent, the powder particulate matter attached to the well wall affects its sealing effect, resulting in a deterioration of adhesion ability and affecting the sealing effect.

Method used

By preparing pellet materials containing calcium carbonate particles and resin particles, and forming positive ions and rich pore structures on their surfaces, combining long lint cotton fibers and defat cotton fibers, the electrostatic adsorption and adhesion capacity of temporary plugging agents is improved, and specific stirring is used and the heating treatment method to prepare temporary plugging agent.

Benefits of technology

The adhesion effect and sealing time of the temporary plugging agent on the well wall are improved, the compressive resistance is enhanced, and the self-cleaning and better sealing effect of the well wall powder particles is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320625A_ABST
    Figure CN119320625A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of temporary plugging agents for oil exploitation, in particular to a temporary plugging agent for plugging drilling cracks in oil exploitation and a preparation method of the temporary plugging agent. The temporary plugging agent comprises the following raw materials in parts by weight: 80-100 parts of granules, 20-30 parts of a fiber material, 10-20 parts of quartz sand, 4-8 parts of a nucleating agent, 4-8 parts of a compatilizer, 2-4 parts of a lubricant and 2-4 parts of a stabilizer. According to the invention, ions on the surfaces of the particles can form continuous conductive channels among the particles, so that the temporary plugging agent is endowed with electric ion performance, when the temporary plugging agent is added into a well for plugging treatment, the temporary plugging agent can generate electrostatic adsorption on powder particles on the wall of the well during flowing, and the powder particles are uniformly dispersed along with the flowing of the flowing temporary plugging agent. When the temporary plugging agent is used, powder particles on the well wall can be sucked into the temporary plugging agent, the effect of self-cleaning of dust particles on the well wall is achieved, the attachment effect of the temporary plugging agent on the well wall can be improved, and therefore the plugging effect of the temporary plugging agent is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of temporary plugging agents for oil production, in particular to a temporary plugging agent for plugging cracks in oil production drilling and a preparation method thereof. Background Art

[0002] Oil well temporary plugging agent is a functional material used in the process of oil extraction. During drilling operations, when cracks or high permeability layers appear in the formation, the temporary plugging agent can temporarily block these channels. Its main function is to prevent excessive leakage of working fluids such as drilling fluid and fracturing fluid, and avoid damage to the formation. At the same time, it can also achieve selective plugging, guide the working fluid into the target formation area, and improve the efficiency of oil reservoir extraction.

[0003] In the prior art, when a temporary plugging agent is used to plug cracks in oil drilling, a large amount of powdered granular material will adhere to the well wall. After the temporary plugging agent is added, the powdered granular material will be between the well wall and the temporary plugging agent, which makes the temporary plugging agent's adhesion to the well wall worse, affecting the plugging effect of the temporary plugging agent. Based on this, the present invention provides a temporary plugging agent for plugging cracks in oil drilling and a preparation method thereof. Summary of the invention

[0004] The purpose of the present invention is to provide a temporary plugging agent for plugging cracks in oil production drilling and a preparation method thereof. The temporary plugging agent prepared by the present invention not only has good plugging time performance, but also has excellent compressive resistance, which effectively improves the plugging performance of the temporary plugging agent.

[0005] To achieve the above object, the present invention provides the following technical solutions: In a first aspect, the present invention provides a temporary plugging agent for sealing cracks in oil drilling, comprising the following raw materials in parts by weight: 80 to 100 granular materials, 20 to 30 parts of fiber materials, 10 to 20 parts of quartz sand, 4 to 8 parts of nucleating agents, 4 to 8 parts of compatibilizers, 2 to 4 parts of lubricants and 2 to 4 parts of stabilizers.

[0006] Furthermore, the nucleating agent is at least one of sodium glutarate, talcum powder and calcium carbonate.

[0007] Furthermore, the quartz sand has a particle size of ≤15 μm.

[0008] Furthermore, the nucleating agent is selected from at least one of sodium glutarate, talcum powder, and calcium carbonate, and the compatibilizer is selected from at least one of polycarbonate, silicone resin, and polymethylsiloxane.

[0009] Furthermore, the lubricant is selected from at least one of calcium stearate, pentaerythritol stearate, and polyethylene wax, and the stabilizer is selected from at least one of tribasic lead sulfate and dibutyltin dilaurate.

[0010] Furthermore, the fiber material is a combination of long-staple cotton fiber and absorbent cotton fiber, the mass ratio of the long-staple cotton fiber to the absorbent cotton fiber is 4:6, and the long-staple cotton fiber and the absorbent cotton fiber are selected to have a length of 1 to 3 mm.

[0011] Furthermore, the granular material is a combination of calcium carbonate particles and resin particles, the mass ratio of the calcium carbonate particles to the resin particles is 4:3, and the calcium carbonate particles and the resin particles have a particle size of 5 to 8 μm.

[0012] Furthermore, the granular material is prepared by the following method: adding hydrogen peroxide solution to a mixture of calcium carbonate particles and resin particles, the mass of the hydrogen peroxide solution being 50-60% of the mass of the calcium carbonate particles, stirring and mixing, and then standing to react for 2-4 hours, filtering and washing after the reaction, and sending it into an oven set at 70-80°C for drying for 45-55 minutes to obtain a dried material, adding ammonium nitrate solution to the dried material, the mass of the ammonium nitrate solution being 60-80% of the mass of the calcium carbonate particles, continuously stirring and reacting for 40-50 minutes, filtering and washing after the reaction, and sending it into an oven set at 60-70°C for drying for 45-55 minutes to obtain a granular material.

[0013] Furthermore, the concentration of the hydrogen peroxide solution is selected to be 3-5%, and the concentration of the ammonium nitrate solution is selected to be 0.3-0.5 mol / L.

[0014] In a second aspect, the present invention provides a method for preparing a temporary plugging agent for plugging cracks in oil production drilling, comprising the following steps: S1: Weigh the granular material, fiber material and quartz sand as needed and add them into the mixing equipment, set the speed to 300-500r / min and stir for 12-16min; S2: Add nucleating agent, compatibilizer, lubricant and stabilizer to the mixture of granular material, fiber material and quartz sand as needed, set the mixing equipment to 800-1000r / min and continue stirring for 20-24min; S3: Add the mixture of granular material, fiber material, quartz sand, nucleating agent, compatibilizer, lubricant and stabilizer into a twin-screw extruder, set the temperature to 180-200°C, cool and cut the material after discharge, and obtain a temporary plugging agent for plugging cracks in oil drilling.

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. In the present invention, by preliminarily treating the granular material in the preparation process of the temporary plugging agent, ammonium nitrate will dissociate into ammonium ions and nitrate ions in the aqueous solution, and these ions will be adsorbed on the surface of the calcium carbonate particles and the resin particles, so that the calcium carbonate particles and the resin particles carry positive ions. When a plurality of particles adsorbed with ammonium nitrate ions are in contact with each other, the ions on the surface of the particles can form a continuous conductive channel between the particles, so that the temporary plugging agent is endowed with ionic properties. When the temporary plugging agent is added into the well for plugging treatment, the temporary plugging agent can generate electrostatic adsorption on the powder particles on the well wall when flowing. With the flow of the flowing temporary plugging agent, the powder particles on the well wall will be sucked into the temporary plugging agent, achieving the effect of self-cleaning the dust particles on the well wall, which can improve the adhesion effect of the temporary plugging agent on the well wall, thereby improving the plugging effect of the temporary plugging agent.

[0016] 2. In the present invention, after the mixture of calcium carbonate particles and resin particles is soaked in a hydrogen peroxide solution, the surfaces of the calcium carbonate particles and the resin particles can be micro-corroded to form a rich pore structure on the surfaces of the calcium carbonate particles and the resin particles. When the plugging agent enters the well for plugging, the rich pore structure on the surfaces of the calcium carbonate particles and the resin particles can be used to adsorb a large amount of powder particles, thereby further improving the adhesion effect of the temporary plugging agent on the well wall. While increasing the plugging time, due to the good adhesion, the compressive strength of the plugging position can also be improved.

[0017] 3. In the present invention, by adding long-staple cotton fiber and absorbent cotton fiber during the preparation process, the cotton fiber can enhance flexibility. The surface of the cotton fiber has many hydroxyl active groups, which can uniformly adsorb powder particles to prevent excessive agglomeration of powder particles after adsorption, effectively reduce the powder particles between the temporary plugging agent and the well wall, and further improve the overall performance of the temporary plugging agent. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The invention proposes a temporary plugging agent for plugging cracks in oil drilling and a flow chart of its preparation method. DETAILED DESCRIPTION

[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0020] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the accompanying drawings.

[0021] The present embodiment provides a temporary plugging agent for plugging cracks in oil drilling, comprising the following raw materials in parts by weight: 80 to 100 parts of granular material, 20 to 30 parts of fiber material, 10 to 20 parts of quartz sand, 4 to 8 parts of nucleating agent, 4 to 8 parts of compatibilizer, 2 to 4 parts of lubricant and 2 to 4 parts of stabilizer.

[0022] In some embodiments, the nucleating agent is at least one of sodium glutarate, talc, and calcium carbonate.

[0023] In some embodiments, the quartz sand has a particle size of ≤15 μm.

[0024] In some embodiments, the nucleating agent is at least one of sodium glutarate, talc, and calcium carbonate, and the compatibilizer is at least one of polycarbonate, silicone resin, and polymethylsiloxane.

[0025] In some embodiments, the lubricant is selected from at least one of calcium stearate, pentaerythritol stearate, and polyethylene wax, and the stabilizer is selected from at least one of tribasic lead sulfate and dibutyltin dilaurate.

[0026] In some embodiments, the fiber material is a combination of long-staple cotton fiber and absorbent cotton fiber, the mass ratio of the long-staple cotton fiber to the absorbent cotton fiber is 4:6, and the length of the long-staple cotton fiber and the absorbent cotton fiber is 1 to 3 mm.

[0027] In this embodiment, by adding long-staple cotton fiber and absorbent cotton fiber during the preparation process, the cotton fiber can enhance flexibility. The surface of the cotton fiber has many hydroxyl active groups, which can evenly adsorb powder particles to prevent excessive agglomeration of powder particles after adsorption, effectively reduce the powder particles between the temporary plugging agent and the well wall, and further improve the overall performance of the temporary plugging agent.

[0028] In some embodiments, the particulate material is a combination of calcium carbonate particles and resin particles, the mass ratio of calcium carbonate particles to resin particles is 4:3, and the calcium carbonate particles and resin particles have a particle size of 5 to 8 μm.

[0029] In some embodiments, the granular material is prepared by the following method: adding hydrogen peroxide solution to a mixture of calcium carbonate particles and resin particles, the mass of the hydrogen peroxide solution is 50-60% of the mass of the calcium carbonate particles, stirring and mixing, and then standing to react for 2-4 hours, filtering and washing after the reaction, sending it into an oven set at 70-80°C for drying for 45-55 minutes to obtain a dried material, adding ammonium nitrate solution to the dried material, the mass of the ammonium nitrate solution is 60-80% of the mass of the calcium carbonate particles, continuing to stir and react for 40-50 minutes, filtering and washing after the reaction, sending it into an oven set at 60-70°C for drying for 45-55 minutes to obtain a granular material.

[0030] In this embodiment, ammonium nitrate will dissociate into ammonium ions and nitrate ions in an aqueous solution, and these ions will be adsorbed on the surface of calcium carbonate particles and resin particles, so that the calcium carbonate particles and resin particles carry positive ions. When multiple particles adsorbed with ammonium nitrate ions come into contact with each other, the ions on the surface of the particles can form a continuous conductive channel between the particles, so that the temporary plugging agent is endowed with ionic properties. When the temporary plugging agent is added into the well for plugging treatment, the temporary plugging agent can generate electrostatic adsorption on the powder particles on the well wall when it flows. As the flowing temporary plugging agent flows, the powder particles on the well wall will be sucked into the interior of the temporary plugging agent, achieving the effect of self-cleaning the dust particles on the well wall, which can improve the adhesion effect of the temporary plugging agent to the well wall, thereby improving the plugging effect of the temporary plugging agent.

[0031] In some embodiments, the concentration of the hydrogen peroxide solution is 3-5%, and the concentration of the ammonium nitrate solution is 0.3-0.5 mol / L.

[0032] In this embodiment, after the mixture of calcium carbonate particles and resin particles is soaked in a hydrogen peroxide solution, the surfaces of the calcium carbonate particles and the resin particles can be micro-corroded to form a rich pore structure on the surfaces of the calcium carbonate particles and the resin particles. When the plugging agent enters the well for plugging, the rich pore structure on the surfaces of the calcium carbonate particles and the resin particles can be used to adsorb a large amount of powder particles, thereby further improving the adhesion effect of the temporary plugging agent on the well wall. While increasing the plugging time, due to the good adhesion, the compressive strength of the plugging position can also be improved.

[0033] In some embodiments, a method for preparing a temporary plugging agent for plugging cracks in oil drilling comprises the following steps: S1: Weigh the granular material, fiber material and quartz sand as needed and add them into the mixing equipment, set the speed to 300-500r / min and stir for 12-16min; S2: Add nucleating agent, compatibilizer, lubricant and stabilizer to the mixture of granular material, fiber material and quartz sand as needed, set the mixing equipment to 800-1000r / min and continue stirring for 20-24min; S3: Add the mixture of granular material, fiber material, quartz sand, nucleating agent, compatibilizer, lubricant and stabilizer into a twin-screw extruder, set the temperature to 180-200°C, cool and cut the material after discharge, and obtain a temporary plugging agent for plugging cracks in oil drilling.

[0034] Based on the above embodiments, the inventors also conducted the following experiments:

[0035] It should be noted that the raw materials used in the following experiments are all commercially available raw materials.

[0036] Experiment 1:

[0037] Raw material preparation: 80 parts of granular material, 20 parts of fiber material, 10 parts of quartz sand, 4 parts of nucleating agent, 4 parts of compatibilizer, 2 parts of lubricant and 2 parts of stabilizer; Among them, the quartz sand is selected with a particle size of ≤15μm, the nucleating agent is sodium glutarate, the compatibilizer is polycarbonate, the lubricant is calcium stearate, the stabilizer is tribasic lead sulfate, the fiber material is a combination of long-staple cotton fiber and absorbent cotton fiber, the mass ratio of long-staple cotton fiber to absorbent cotton fiber is 4:6, and the length of long-staple cotton fiber and absorbent cotton fiber is 1mm, the particle material is a combination of calcium carbonate particles and resin particles, the mass ratio of calcium carbonate particles to resin particles is 4:3, and the particle size of calcium carbonate particles and resin particles is 5μm; Preparation of granular material: add hydrogen peroxide solution to the mixture of calcium carbonate particles and resin particles, the mass of hydrogen peroxide solution is 50% of the mass of calcium carbonate particles, stir and mix, let it stand for reaction for 2 hours, filter and wash after reaction, send it into an oven set at 70°C for drying for 45 minutes to obtain dried material, add ammonium nitrate solution to the dried material, the mass of ammonium nitrate solution is 60% of the mass of calcium carbonate particles, continue stirring and reacting for 40 minutes, filter and wash after reaction, send it into an oven set at 60°C for drying for 45 minutes, wherein the concentration of hydrogen peroxide solution is 3%, and the concentration of ammonium nitrate solution is 0.3 mol / L; Preparation of temporary plugging agent: weigh granular material, fiber material and quartz sand as needed and add them into the mixing equipment, set 300r / min and stir for 12min, weigh and add nucleating agent, compatibilizer, lubricant and stabilizer into the mixture of granular material, fiber material and quartz sand as needed, set the mixing equipment to 800r / min and continue stirring for 20min, add the mixture of granular material, fiber material, quartz sand, nucleating agent, compatibilizer, lubricant and stabilizer into the twin-screw extruder, set the temperature to 180℃, and cool and cut the material after discharge.

[0038] Experiment 2:

[0039] Raw material preparation: 90 parts of granular material, 25 parts of fiber material, 15 parts of quartz sand, 6 parts of nucleating agent, 6 parts of compatibilizer, 3 parts of lubricant and 3 parts of stabilizer; Among them, the quartz sand is selected to have a particle size of ≤15μm, the nucleating agent is a combination of sodium glutarate, talc and calcium carbonate, the compatibilizer is a combination of polycarbonate and silicone resin, the lubricant is pentaerythritol stearate, the stabilizer is dibutyltin dilaurate, the fiber material is a combination of long-staple cotton fiber and absorbent cotton fiber, the mass ratio of long-staple cotton fiber to absorbent cotton fiber is 4:6, the length of long-staple cotton fiber and absorbent cotton fiber is 2mm, the particle material is a combination of calcium carbonate particles and resin particles, the mass ratio of calcium carbonate particles to resin particles is 4:3, and the particle size of calcium carbonate particles and resin particles is 6μm; Preparation of granular material: add hydrogen peroxide solution to the mixture of calcium carbonate particles and resin particles, the mass of hydrogen peroxide solution is 55% of the mass of calcium carbonate particles, stir and mix, let it stand for reaction for 3 hours, filter and wash after reaction, send it into an oven set at 75°C for drying for 50 minutes to obtain dried material, add ammonium nitrate solution to the dried material, the mass of ammonium nitrate solution is 70% of the mass of calcium carbonate particles, continue stirring and reacting for 45 minutes, filter and wash after reaction, send it into an oven set at 65°C for drying for 50 minutes, wherein the concentration of hydrogen peroxide solution is 4%, and the concentration of ammonium nitrate solution is 0.4 mol / L; Preparation of temporary plugging agent: weigh granular material, fiber material and quartz sand as needed and add them into the mixing equipment, set 400r / min and stir for 14min, weigh and add nucleating agent, compatibilizer, lubricant and stabilizer into the mixture of granular material, fiber material and quartz sand as needed, set the mixing equipment to 900r / min and continue stirring for 22min, add the mixture of granular material, fiber material, quartz sand, nucleating agent, compatibilizer, lubricant and stabilizer into the twin-screw extruder, set the temperature to 190℃, and cool and cut the material after discharge.

[0040] Experiment 3:

[0041] Raw material preparation: 100 parts of granular material, 30 parts of fiber material, 20 parts of quartz sand, 8 parts of nucleating agent, 8 parts of compatibilizer, 4 parts of lubricant and 4 parts of stabilizer; Among them, the quartz sand is selected with a particle size of ≤15μm, the nucleating agent is calcium carbonate, the compatibilizer is polymethylsiloxane, the lubricant is polyethylene wax, the stabilizer is dibutyltin dilaurate, the fiber material is a combination of long-staple cotton fiber and absorbent cotton fiber, the mass ratio of long-staple cotton fiber to absorbent cotton fiber is 4:6, and the length of long-staple cotton fiber and absorbent cotton fiber is 3mm, the particle material is a combination of calcium carbonate particles and resin particles, the mass ratio of calcium carbonate particles to resin particles is 4:3, and the particle size of calcium carbonate particles and resin particles is 8μm; Preparation of granular material: add hydrogen peroxide solution to the mixture of calcium carbonate particles and resin particles, the mass of hydrogen peroxide solution is 60% of the mass of calcium carbonate particles, stir and mix, let it stand for reaction for 4 hours, filter and wash after reaction, send it into an oven set at 80°C for drying for 55 minutes to obtain dried material, add ammonium nitrate solution to the dried material, the mass of ammonium nitrate solution is 80% of the mass of calcium carbonate particles, continue stirring and reacting for 50 minutes, filter and wash after reaction, send it into an oven set at 70°C for drying for 55 minutes, wherein the concentration of hydrogen peroxide solution is 5%, and the concentration of ammonium nitrate solution is 0.5 mol / L; Preparation of temporary plugging agent: weigh granular material, fiber material and quartz sand as needed and add them into the mixing equipment, set 500r / min and stir for 16min, weigh and add nucleating agent, compatibilizer, lubricant and stabilizer into the mixture of granular material, fiber material and quartz sand as needed, set the mixing equipment to 1000r / min and continue stirring for 24min, add the mixture of granular material, fiber material, quartz sand, nucleating agent, compatibilizer, lubricant and stabilizer into a twin-screw extruder, set the temperature to 200℃, and cool and cut the material after discharge.

[0042] Comparative Example 1: The difference between this comparative example and Experiment 1 is that: In this comparative example, an equal amount of a mixture of calcium carbonate particles and resin particles was used to replace the granular material.

[0043] Comparative Example 2: The difference between this comparative example and Experiment 1 is that: No fiber material was added in this comparative example.

[0044] Comparative Example 3: The difference between this comparative example and Experiment 1 is that: No quartz sand was added in this comparative example.

[0045] Comparative Example 4: The difference between this comparative example and Experiment 1 is that: In this comparative example, the mixture of calcium carbonate particles and resin particles was immersed in an ammonium nitrate solution.

[0046] Performance test: The temporary plugging agents for plugging cracks in oil drilling prepared in Experiment 1, Experiment 2, Experiment 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 were tested for performance, and the test data obtained are recorded in the following table:

[0047] In the performance test, the detection method of the plugging time is as follows: the temporary plugging agents for plugging cracks in oil drilling prepared in Experiment 1, Experiment 2, Experiment 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 are respectively made into suspensions, and then a sand-filled tube model is used to simulate the structure of the oil well formation, and the suspension is injected into the sand-filled tube at a speed of 5 ml / min. After the sand-filled tube is filled, the plugging status in each sand-filled tube is observed.

[0048] The test method for compressive performance is as follows: after filling the sand filling pipe with the same steps as above, use a testing machine to drive a circular plate with a diameter of 10 mm to uniformly pressurize the sand filling pipe, and observe the blocking state in the sand filling pipe during the pressurization process.

[0049] Among them, the temporary plugging agents for sealing cracks in oil drilling prepared in Experiment 1, Experiment 2, Experiment 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 had plugging time test results of 21 days, 22 days, 20 days, 9 days, 16 days, 11 days and 12 days, respectively; the temporary plugging agents for sealing cracks in oil drilling prepared in Experiment 1, Experiment 2, Experiment 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 had compressive performance test results of 85.5 MPa, 86.4 MPa, 85.1 MPa, 41.6 MPa, 50.7 MPa, 41.7 MPa and 48.6 MPa, respectively.

[0050] It can be seen that the plugging time and compressive performance data of the temporary plugging agents for plugging cracks in oil drilling prepared in Comparative Examples 1, 2, 3 and 4 are lower than those in Experiments 1, 2 and 3; this shows that: through the preliminary treatment of the granular material in the preparation process of the temporary plugging agent, ammonium nitrate will dissociate into ammonium ions and nitrate ions in the aqueous solution, and these ions will be adsorbed on the surface of the calcium carbonate particles and the resin particles, so that the calcium carbonate particles and the resin particles carry positive ions. When a plurality of particles adsorbed with ammonium nitrate ions are in contact with each other, the ions on the surface of the particles can form a continuous conductive channel between the particles, so that the temporary plugging agent is endowed with ionic properties. When the temporary plugging agent is added into the well for plugging treatment, the temporary plugging agent can generate electrostatic adsorption on the powder particles on the well wall when it flows. As the temporary plugging agent flows With the flow of the temporary plugging agent, the powder particles on the well wall will be sucked into the interior of the temporary plugging agent, achieving the effect of self-cleaning the dust particles on the well wall, which can improve the adhesion effect of the temporary plugging agent to the well wall, thereby improving the plugging effect of the temporary plugging agent. After the mixture of calcium carbonate particles and resin particles is soaked in hydrogen peroxide solution, the surface of the calcium carbonate particles and the resin particles can be micro-corroded to form a rich pore structure on the surface of the calcium carbonate particles and the resin particles. When the plugging agent enters the well for plugging, the rich pore structure on the surface of the calcium carbonate particles and the resin particles can be used to adsorb a large amount of powder particles, thereby further improving the adhesion effect of the temporary plugging agent to the well wall. While increasing the plugging time, due to the good adhesion, the pressure resistance of the plugging position can also be improved.

[0051] By comparing and analyzing the relevant data in the table, it can be seen that the temporary plugging agent for plugging cracks in oil production drilling prepared by the present invention not only has good plugging time performance, but also has excellent compressive resistance. This shows that the temporary plugging agent for plugging cracks in oil production drilling provided by the present invention and the preparation method thereof have a broader market prospect and are more suitable for promotion.

[0052] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0053] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A temporary plugging agent for plugging cracks in oil drilling, characterized by: The invention comprises the following raw materials in parts by weight: 80 to 100 parts of granular material, 20 to 30 parts of fiber material, 10 to 20 parts of quartz sand, 4 to 8 parts of nucleating agent, 4 to 8 parts of compatibilizer, 2 to 4 parts of lubricant and 2 to 4 parts of stabilizer; The granular material is a combination of calcium carbonate particles and resin particles. The granular material is prepared by the following method: adding hydrogen peroxide solution to the mixture of calcium carbonate particles and resin particles, stirring and mixing, and then standing to react for 2 to 4 hours, filtering and washing after the reaction, sending it into an oven set at 70 to 80° C. for drying for 45 to 55 minutes to obtain a dried material, adding ammonium nitrate solution to the dried material, continuously stirring and reacting for 40 to 50 minutes, filtering and washing after the reaction, and sending it into an oven set at 60 to 70° C. for drying for 45 to 55 minutes to obtain a granular material.

2. The temporary plugging agent for plugging cracks in oil drilling according to claim 1, characterized in that: The nucleating agent is at least one of sodium glutarate, talcum powder and calcium carbonate.

3. The temporary plugging agent for plugging cracks in oil drilling according to claim 1, characterized in that: The quartz sand has a particle size of ≤15 μm.

4. The temporary plugging agent for plugging cracks in oil drilling according to claim 1, characterized in that: The compatibilizer is selected from at least one of polycarbonate, silicone resin and polysiloxane.

5. The temporary plugging agent for plugging cracks in oil drilling according to claim 1, characterized in that: The lubricant is selected from at least one of calcium stearate, pentaerythritol stearate, and polyethylene wax, and the stabilizer is selected from at least one of tribasic lead sulfate and dibutyltin dilaurate.

6. The temporary plugging agent for plugging cracks in oil drilling according to claim 1, characterized in that: The fiber material is a combination of long-staple cotton fiber and absorbent cotton fiber, the mass ratio of the long-staple cotton fiber to the absorbent cotton fiber is 4:6, and the length of the long-staple cotton fiber and the absorbent cotton fiber is 1-3 mm.

7. The temporary plugging agent for plugging cracks in oil drilling according to claim 1, characterized in that: The mass ratio of the calcium carbonate particles to the resin particles is 4:3, and the calcium carbonate particles and the resin particles have a particle size of 5 to 8 μm.

8. The temporary plugging agent for plugging cracks in oil drilling according to claim 1, characterized in that: The mass of the hydrogen peroxide solution is 50-60% of the mass of the calcium carbonate particles, and the mass of the ammonium nitrate solution is 60-80% of the mass of the calcium carbonate particles.

9. The temporary plugging agent for plugging cracks in oil drilling according to claim 1, characterized in that: The concentration of the hydrogen peroxide solution is 3-5%, and the concentration of the ammonium nitrate solution is 0.3-0.5 mol / L.

10. A method for preparing a temporary plugging agent for plugging cracks in oil drilling, characterized in that: Used to prepare the temporary plugging agent for plugging cracks in oil drilling according to any one of claims 1 to 9, the method comprises the following steps: S1: Weigh the granular material, fiber material and quartz sand as needed and add them into the mixing equipment, set the speed to 300-500r / min and stir for 12-16min; S2: Add nucleating agent, compatibilizer, lubricant and stabilizer to the mixture of granular material, fiber material and quartz sand as needed, set the mixing equipment to 800-1000r / min and continue stirring for 20-24min; S3: Add the mixture of granular material, fiber material, quartz sand, nucleating agent, compatibilizer, lubricant and stabilizer into a twin-screw extruder, set the temperature to 180-200°C, cool and cut the material after discharge, and obtain a temporary plugging agent for plugging cracks in oil drilling.

Citation Information

Patent Citations

  • High temperature resistant shielding and temporary plugging agent, preparation method and application

    CN109401739A

  • Composite plugging agent for well drilling and application thereof

    CN110872502A

  • Fiber polymer plugging agent for drilling fluid and preparation method thereof

    CN115418203A

  • Method for enlarging safety density window of well drilling borehole formation

    WO2019095420A1